The Effect of Emotion Regulation on Teachers’ Work Motivation at the Pembina State Special School, North Sumatra Province - Fahri, Syahrul; Puspita Sari, Inggrit; Yulianti Sirega, Chairiah; Cintami Saota, Anselma Lilis (Rifa'Institute, 2026)
Introduction: Special School teachers play an important role in special education in accordance with Government Regulation of the Republic of Indonesia No. 72 of 1991, because they not only teach but also accompany students with special needs to develop optimally. This role requires high work motivation, which is also strengthened by the support of family, principals, and colleagues. One of the factors related to motivation is the regulation of emotions, which is the ability to manage, balance, and express emotions adaptively in various situations. Objective: This study aims to determine the influence of emotion regulation on teachers' work motivation in the Special School (Extraordinary School) of the State Coach at the North Sumatra Provincial Level. Method: A quantitative method with a causal approach involved 73 teachers, data were collected through questionnaires and analyzed using simple linear regression. Result and Discussion: Results showed a significant influence (R²=0.415; p=0.000<0.05), so that 41.5% of motivational variations were explained by emotion regulation and 58.5% by other factors. Conclusion: These findings confirm the need for emotional regulation training and organizational support to maintain work motivation, so that Special School teachers are more resilient to the demands of continuous daily student learning and behavior.